2010
DOI: 10.1016/j.ymgme.2010.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Thermolability of mutant MMACHC protein in the vitamin B12-responsive cblC disorder

Abstract: Methylmalonic aciduria and homocystinuria, cblC type, is the most common inborn error of cellular vitamin B12 metabolism. We previously showed that the protein carrying the mutation responsible for late-onset cblC (MMACHC-R161Q), treatable with high dose OHCbl, is able to bind OHCbl with wild-type affinity, leaving undetermined the disease mechanism involved [Froese et al., Mechanism of responsiveness, Mol. Genet. Metab. (2009).]. To assess whether the mutation renders the protein unstable, we investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 45 publications
4
49
1
1
Order By: Relevance
“…In the absence of cobalamins, total scattering intensity increased exponentially above 48°C for MMADHCΔ1-12 and above 52°C for MMADHCΔ1-61, a transition point reflecting the melting temperature (T m ) for proteins [40,41]. These values are significantly higher than that reported for full length MMACHC (~40°C) [15,18]. Furthermore, the addition of 10-fold molar excesses of the four cobalamins to either MMADHC construct did not shift the transition points to a higher temperature, indicating no apparent stabilization by cobalamin.…”
Section: Mmadhc Does Not Bind Cobalaminmentioning
confidence: 75%
See 1 more Smart Citation
“…In the absence of cobalamins, total scattering intensity increased exponentially above 48°C for MMADHCΔ1-12 and above 52°C for MMADHCΔ1-61, a transition point reflecting the melting temperature (T m ) for proteins [40,41]. These values are significantly higher than that reported for full length MMACHC (~40°C) [15,18]. Furthermore, the addition of 10-fold molar excesses of the four cobalamins to either MMADHC construct did not shift the transition points to a higher temperature, indicating no apparent stabilization by cobalamin.…”
Section: Mmadhc Does Not Bind Cobalaminmentioning
confidence: 75%
“…Recent evidence suggests possible localization to the mitochondrion [14] despite its lacking a predicted mitochondrial leader sequence. MMACHC binds Cbl [15][16][17] in a base-off conformation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Froese et al demonstrated that MMACHC is naturally thermolabile (T m = 39 ° C) and that some of the most frequent mutations that occur in humans exacerbate this property [ 39 ] as well as its ability to bind Cbls [ 40 ]. Studies with the bovine isoform of MMACHC revealed that the reduced form of glutathione stabilizes MMACHC, suggesting that intracellular redox control could play a role in the regulation of the protein ' s lifetime [ 41 -44 ].…”
Section: Biophysical and Structural Characterization Of The B 12 -Promentioning
confidence: 99%
“…Mutations at Arg-161 are among the most common of the missense mutations leading to the cblC disorder, and depending on the nature of the substitution, these mutations are associated with either early (R161G) or late (R161Q) onset of the disease (20). The R161Q mutant has been characterized minimally, reported to decrease the T m of CblC by 2°C (25) and the MeCbl dealkylation activity ϳ10-fold (24).…”
mentioning
confidence: 99%